Dietary calcium intake in primary hyperparathyroidism and in its normocalcemic variant: a case-control study - Bisceglia, Nicolò; Malagrinò, Matteo; Piazza, Anna; Vandi, Giulia; Repaci, Andrea; Pagotto, Uberto; Zavatta, Guido (Frontiers in Endocrinology, 2025)
IntroductionNormocalcemic primary hyperparathyroidism (NHPT) is considered to be an early stage in the evolution of primary hyperparathyroidism (PHPT). To formulate a correct diagnosis, secondary hyperparathyroidism due to low calcium intake must be excluded. Whether dietary calcium intake might affect the clinical presentation of PHPT or NHPT has never been addressed consistently.ObjectiveTo describe patients with a diagnosis of NHPT or PHPT in relation to their calcium intake, through three standard validated questionnaires; to describe clinical, biochemical and radiological features of NHPT and PHPT patients compared to each other and to a control group.DesignCross-sectional study.SettingOutpatient, single academic medical center.Patients109 consecutive women recruited from February 2021 through April 2023. 54 patients with mild primary hyperparathyroidism (PHPT or NHPT) were age-matched with 55 unselected women undergoing bone density test screening due to recently diagnosed hormone-positive breast cancer. NHPT diagnosis was based on multiple determinations of both total and albumin-corrected serum calcium.InterventionsAdministration of all the following during routine endocrine consultation: a country-specific food-frequency questionnaire (LOC), the International Osteoporosis Foundation Calcium Calculator (IOF) and the National Osteoporosis Foundation calcium questionnaire (NOF).Main outcome measuresAny association between dietary calcium intake and clinical, radiological, or biochemical features.ResultsAll three questionnaires confirmed that NHPT patients had similar calcium intake as those with PHPT or controls. Biochemistries and bone turnover markers were similar between the two variants of hyperparathyroidism, except for serum calcium (sCa). NHPT patients had a significantly lower BMD and T-score at one-third distal radius compared to PHPT, while the prevalence of nephrolithiasis and clinical fractures were similar. Multivariate analysis investigating predictors of serum calcium showed that age, eGFR, calcium intake and 25(OH)D did not significantly affect serum calcium, while multivariate analysis investigating predictors of PTH (age, variant NHPT vs. PHPT, eGFR, calcium intake, 25(OH)D, cholecalciferol supplements) showed that calcium intake, variant and renal function, significantly influenced PTH levels.ConclusionsAll patients with primary hyperparathyroidism, particularly those with low dietary calcium intake, should be advised not to restrict dietary calcium to prevent further increase in PTH levels. Whether maintaining adequate calcium intake might positively impact bone density or biochemistries in patients refraining from surgery, should be addressed in longitudinal studies.